Analisis Hukum Terhadap Penyelesaian Diluar Pengadilan (Diversi) Dalam Tindak Pidana Kekerasan Yang Dilakukan Oleh Anak Di Wilayah Polresta Kota Binjai - Muhammad Rizal Aulia Lubis; Ediwarman Ediwarman; Marlina Marlina; Jusmadi Sikumbang (USU LAW JOURNAL, 2019)
Abstract. Definition of diversion in Law No. 11 of 2012 Article 1 Paragraph 7 concerning the juvenile justice system. meaning "Diversion is the transfer of settlement of child cases from criminal justice processes to processes outside of criminal justice. No government regulation. 65 of 2015 concerning guidelines for the implementation of diversion and handling of children not yet (12 twelve) years old. Secret telegram letter (TR) of the Kabareskrim Polri  No.Pol.TR/1124/XI/2006 and No.Pol Police's secret telegram (TR) kabareskrim. TR / 395 / DIT.I / VI / 2008 concerning the implementation of diversion and restorative justice in handling cases of child offenders and fulfillment of the best interests of children in the case of children both as perpetrators, victims or witnesses. Case child commits a crime of violence in the Regional Police of the city of Binjai in North Sumatra province, a child under age has committed a crime of violence against other people. From this case, the Polresta Binjai sought a diversion process with a restorative justice approach. In the court decision of class 1-B Binjai No.11 / Pid.Sus.Anak / 2015 / PN.Bnj concerning the diversion decree.              From the results research conducted, it can at concluded as following P ertama, In carrying out diversion, the regulations used are Law No. 11 of 2012 concerning the Child Criminal Justice System and instructions for the implementation of diversion issued by the National Police Kabareskrim namely Kabareskrim POLRI Secret Telegraph TR / 1124 / XI / 2006 and TR / 395 / DIT, VI / 2008 concerning implementation of diversion and restorative justice in handling cases of child offenders and fulfillment of the best interests of children in the case of children both as perpetrators, victims or witnesses, Government Regulation No.65 of 2015 concerning guidelines for the implementation of diversion and handling of children who are not (12 twelve) years old. Secondly, the factors that led to the crime of child abuse as perpetrators in the Binjai City Police Department consisted of economic factors, social factors, psychological factors. Of the three factors, psychological factors are the underlying factor in the child committing violence in this case. Psychological factors are vital for each human person in carrying out life in society. Unstable psychological factors in adolescents can cause disparities with adults and parents due to differences in age and pivotal patterns of their own actions and behaviors, psychological factors are behaviors / characteristics or personality of humans both seen from within and from outside on him, in this case the children always have a psychology that is still unstable and tends to be easily incited and act without thinking. Third, the non-criminal policy towards the completion of children who are perpetrators of violent crimes in the Polriesta Binjai area, namely conducting counseling, carrying out counseling for schools, carrying out routine raids, carrying out social services. Public participation in this regard Enabling activities among adolescents, Me mberiakan motivation or advice to children, provide religious education.   Keywords : diversion , children , violence